Asymmetrical Relations in Audiovisual Translation in Brazil: A Corpus-based investigation of Fixed Expressions - Domingos Soares (Ilha do Desterro)
This study aims to investigate, in dubbed and subtitled versions of the films Madagascar (2005) and Ice Age (2002), how fixed expressions (Moon, 1998) are translated in dubbing and subtitling methods and to examine how employing domestication and foreignisation (Venuti, 1995) can undermine or reinforce the asymmetrical relations, here defined by globalisation as discussed by Venuti (1998) and Cronin (2003, 2009). The analysis is carried out through reference and parallel corpus (Baker, 1995). Final results show that subtitling, rather than dubbing, is more prone to adopt foreignising strategies with regard to the translation of fixed expressions. Additionally, there have been identified, in the subtitled versions of the corpus, translation instances that deliberately move away from target language fixed expressions.